UNSUR-UNSUR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KOTA TANGERANG - REGINA HANJAYA; Haryo Suparmun (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
Tax compliance is very important, not only for the taxpayers to elude the tax sanction, but also for the Directorate General of Taxation to collect tax revenues. This research aims to find out the impact of tax sanctions, tax awareness, tax socialization, tax knowledge, tax officer services, and modern tax administration systems on the taxpayers compliance. The research object is an individual taxpayer in Tangerang City. The questionnaires were disseminated via google form to collect the data. The purposive sampling method was used for sample selection and 82 respondents were selected and analyzed using multiple regression method. The results show that tax sanctions, tax socialization and tax knowledge have significant positive impact on taxpayers compliance. Meanwhile, tax awareness, tax officer services and modern tax administration systems do not have impact on taxpayers compliance. These results imply that taxpayers comply because they know that the sanctions are quite burdensome if imposed on them, the higher the frequency of tax socialization will increase the willingness of taxpayers in fulfilling tax obligations and tax knowledge which can be obtained by attending formal and informal education on taxation will increase the knowledge and the willingness of the taxpayers to comply to tax regulations.